2020
DOI: 10.1088/1402-4896/ab5288
|View full text |Cite
|
Sign up to set email alerts
|

The effect of giant Kerr nonlinearity on group velocity in a six-level inverted-Y atomic system

Abstract: We propose an analytical model to study the effect of giant Kerr nonlinearity on group velocity of probe light in a six-level inverted-Y atomic system under electromagnetically induced transparency (EIT). In this scheme, a nonlinearity of the medium is enhanced greatly around in three spectral regions corresponding to transparent windows. As a consequence, such a giant Kerr nonlinearity of the medium changes significantly group index for probe light which can obstruct light slowdown. Moreover, this model shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In this section, we apply the analytical model to 87 Rb atom, where |1 and |2 are two hyperfine levels of the ground state |1 = |5S 1/2 , F = 1 and |2 = |5S 1/2 , F = 2 , while |3 and |4 are two hyperfine levels of the excited state |3 = |5P 3/2 , F = 2 and |4 = |5P 3/2 , F = 3 . The atomic parameters are [30,33] 2(a). We can see that when the coupling field is absent, i.e., Ω c = 0, the cross-Kerr nonlinear coefficient is equal to zero (see the dotted line).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we apply the analytical model to 87 Rb atom, where |1 and |2 are two hyperfine levels of the ground state |1 = |5S 1/2 , F = 1 and |2 = |5S 1/2 , F = 2 , while |3 and |4 are two hyperfine levels of the excited state |3 = |5P 3/2 , F = 2 and |4 = |5P 3/2 , F = 3 . The atomic parameters are [30,33] 2(a). We can see that when the coupling field is absent, i.e., Ω c = 0, the cross-Kerr nonlinear coefficient is equal to zero (see the dotted line).…”
Section: Resultsmentioning
confidence: 99%
“…[27,28] In addition, the influences of cross-Kerr nonlinearity on light propagation in transparency media were also performed. [29][30][31][32] Although the cross-Kerr nonlinear effect has been implemented in an ultra-cold four-level N-type atomic system, most applications of Kerr nonlinearity often use hot atomic gas media that is always governed by the Doppler effect. Therefore, the study of the Kerr nonlinear effect in the presence of Doppler broadening is necessary to be applied to photonic devices working under different temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…An enhanced Kerr field has been observed experimentally in Bose condensate sodium atom [22,23]. The slowing down of light has been achieved in the presence of giant Kerr nonlinearity in an inverted Y-type atomic medium [24,25]. The enhancement of cross and self-Kerr nonlinearity in the Doppler broadened medium has been investigated [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, extremely slow or superluminal light pulses were obtained in the EIT [7][8][9] or EIA [10][11][12] regime, respectively. In particular, some recent studies have shown that it is possible to switch between EIT and EIA modes [13] and thus can switch between fast light and slow light by external fields such as using microwave field [14], standing-wave field [15], Kerr field [16][17][18], coherent pump field [19,20], incoherent pump field [21][22][23], static magnetic field [24,25], or using other coherence effects such as spontaneously generated coherence [22,23,[26][27][28][29] and the phase of applied laser fields [30,31] and so on.…”
Section: Introductionmentioning
confidence: 99%